Co-occurrence of depression, anxiety, and perinatal posttraumatic stress in postpartum persons - Shelby Howard; Caitlin Witt; Karla Martin; Ateshi Bhatt; Emily Venable; Sarah Buzhardt; Andrew G. Chapple; Elizabeth F. Sutton (BMC, 2023)
Abstract Background The study aim was to describe the incidence of depression, anxiety, perinatal-post-traumatic stress disorder (PTSD), and their co-occurrences in the early postpartum period in a low-resource OB/GYN clinic serving majority Medicaid-eligible persons. We hypothesized that postpartum persons screening positive for depression will have an increased risk of a positive screen for anxiety and perinatal PTSD. Methods A retrospective study of postpartum persons receiving care in Baton Rouge, Louisiana was conducted using responses abstracted from the electronic medical record (EMR) of the Patient Health Questionnaire-9 (PHQ9), Generalized Anxiety Disorder-7 (GAD7), and Perinatal Post Traumatic Stress Disorder Questionnaire-II (PPQII). Categorical distributions were compared using Fisher exact tests, while t-tests were used to compare continuous covariates. Multivariable logistic regression was used to predict anxiety (GAD7) and perinatal PTSD (PPQII) scores while adjusting for potential confounders, as well as to predict continuous PPQII and GAD7 based on continuous PHQ9 scores. Results There were 613 birthing persons 4-12 weeks postpartum that completed mental health screening (PHQ9, GAD7, and PPQII) between November 2020 and June 2022 as part of routine postpartum care in the clinic. The incidence of screening positive for symptoms of depression (PHQ9 > 4) was 25.4% (n = 156), while the incidence of positive screening for symptoms of anxiety (GAD7 > 4) and perinatal PTSD (PPQII $$\ge$$ ≥ 19) were 23.0% (n = 141) and 5.1% (n = 31) respectively. Postpartum patients with mild anxiety or more (i.e. GAD7 > 4) had 26 times higher odds of screening positive for symptoms of depression (PHQ9 > 4) (adjusted odds ratio [aOR] 26.3; 95% confidence interval [CI] 15.29-46.92; p < 0.001). Postpartum persons with a PPQII score indicating symptoms of perinatal PTSD (PPQII $$\ge$$ ≥ 19) had 44 times higher odds of screening positive for symptoms of depression (PHQ > 4) (aOR 44.14; 95%CI 5.07-5856.17; p < 0.001). Conclusions Depression, anxiety, and perinatal PTSD are each independent risk factors for each other. To comply with the American College of Obstetricians and Gynecologists (ACOG) recommendations, providers should universally screen postpartum persons with validated screening tools for mood disturbances. However, if a complete full mood assessment is not feasible, this study provides evidence to support screening patients for depression, and if the patient screens positive, prompt additional screening for anxiety and perinatal PTSD.